Oxidative Stability of Chicken Thigh Meat after Treatment of Fennel and Savory Essential Oils - Adriana Pavelková; Marek Bobko; Peter Haščík; Miroslava Kačániová; Jana Tkáčová (Scientific Papers Animal Science and Biotechnologies, 2023)
In the present work, the effect of the fennel and savory essential oils on oxidative stability of chicken thigh muscles during chilled storage was investigated. In the experiment were used chickens of hybrid combination Cobb 500 after 42 days of the fattening period. The obtained fresh chicken thigh with skin from left half-carcass were divided into five groups (n = 5): C - control air-packaged group; A1 - vacuum-packaged experimental group; A2 - vacuum-packaged experimental group with EDTA solution 1.50% w/w; A3 - vacuum-packaged experimental group with fennel (Foeniculum vulgare) essential oil at concentrations 0.2% v/w and A4 - vacuum-packaged experimental group with savory (Satureja hortensis) essential oil at concentration 0.2% v/w. The essential oils were applicate on surface chicken thighs. The chicken thighs were packaged using a vacuum packaging machine and stored in refrigerate at 4±0.5 °C. The value of thiobarbituric acid (TBA) expressed as amount of malondialdehyde (MDA) in 1 kg sample was measured during storage in 1st, 4th, 8th, 12th and 16th day. The treatments of chicken thighs with fennel and savory essential oils show statistically significant differences between all testing groups and control group, where higher average value of MDA measured in thigh muscle of broiler chickens was in samples of control group (0.359 mg.kg-1) compared to experimental groups A1 (0.129 mg.kg-1), A2 (0.091 mg.kg-1), A3 (0.084 mg.kg-1) and A4 (0.089 mg.kg-1) after 16-day of chilled storage. Experiment results show that the treatment of chicken thigh with fennel and savory essential oils had positive influence on the reduction of oxidative processes in thigh muscles during chilling storage and use of essential oil is one of the options increase shelf life of fresh chicken meat.